The Effectiveness of Guessing Games Using Flashcards in Improving Vocabulary Mastery of Elementary School Students - Diah Sirrin Nadhirah (Retain: Journal of Research in English Language Teaching, 2025)
This study aims to test the effectiveness of using guessing games with flashcards in improving vocabulary mastery of elementary school students. Vocabulary is an important component in learning English; however, many students still experience difficulties due to low motivation and monotonous teaching methods. Therefore, interactive learning media such as games and visual aids are needed to improve student engagement and learning outcomes. This study used a quantitative approach with a quasi-experimental design. Participants were fifth-grade students of a public elementary school in Surabaya, East Java, who were divided into an experimental class and a control class. The experimental class was taught using guessing games combined with teacher-made flashcards, while the control class was taught using PowerPoint as a learning medium. The sample size in this study was 50 students divided into two classes. Data were collected through a pre-test and post-test and analyzed using a normality test, paired sample t-test, and independent sample t-test with SPSS 26. The results of the calculations from the treatments given showed a significant increase in vocabulary mastery in the experimental class and a significant difference between the post-test scores of the experimental and control classes. In conclusion, guessing games using flashcards are effective in improving vocabulary mastery for early childhood children.